Performance of plasma-assisted chemical looping hydrogen generation at moderate temperature. Issue 5 (6th February 2023) - Wang, Chen; Liu, Tong; Qiu, Yu; Gao, Zixiang; Ou, Wentao; Song, Yiwen; Xiao, Rui; Zeng, Dewang
Abstract : Enhanced hydrogen production performance was achieved via plasma-assisted CLHG with the highest hydrogen yield at 400 °C. Abstract : The thermal sintering of oxygen carriers is a major challenge in the chemical looping hydrogen generation (CLHG) process. Operating the CLHG process at moderate temperatures is a feasible approach to address this issue. Here, we proposed plasma-assisted CLHG to enable hydrogen production at moderate temperatures (300–500 °C) using the oxygen carrier of Fe2 O3 /Al2 O3 . The effects of discharge input power, weight hourly space velocity, and temperatures on the performance were investigated. The results show that enhanced hydrogen production performance was achieved via plasma-assisted CLHG with the highest hydrogen yield of ∼5.2 mmol g −1 and an average hydrogen generation rate of ∼0.29 mmol g −1 min −1 at 400 °C. Characterization demonstrates that plasma deepens the reduction depth from Fe2 O3 → Fe3 O4 to Fe2 O3 → Fe and no spinel phase (FeAl2 O4 ) is detected after 10 cycles. The outstanding performance can be attributed to the activation of plasma on fuel gas and the promotion of lattice oxygen transfer. We anticipate that the promotion effect of plasma on CLHG can be extended to enhance the chemical looping performance for other applications.